Water Inquiry in Geography Education: A Comparative Analysis of Analytical Thinking Enhancement in Hydrosphere Dynamics among Indonesian High School Students - Nissa, Ummah Afiyatun; Hawa, Nabila Nurul (Future Space: Studies in Geo-Education, 2024)
Analytical thinking skills, characterised by complex reasoning and the creation of meaningful learning processes, are crucial for students to master in the evolving educational landscape. Despite the widespread application of inquiry-based learning methods, there needs to be more research exploring the specific effectiveness of the Water Inquiry Learning Model within the context of geography education, particularly in the domain of hydrosphere dynamics. This study aimed to ascertain the influence of the Water Inquiry Learning Model on the analytical thinking abilities of 10th-grade students at SMA Negeri 2 Batu, Malang, Indonesia. Utilising a proper experimental design with a pretest-posttest control group setup, two classes were observed: X-7 (experimental) and X-8 (control). Findings revealed a superior gain score of 72% for class X-7 compared to 45% for class X-8, signifying a significant enhancement in the experimental group's analytical thinking capabilities. These results underscore the powerful impact of the Water Inquiry Learning Model on students' analytical thinking skills. Nonetheless, a deeper understanding and adaptation of the model by students are imperative. Future implementations should provide detailed instructions regarding using biomonitoring cards, a component that may further amplify learning outcomes.